The Influence of Online Customer Review and Rating on Purchase Decisions of L'oréal Product - Hasna, Najmah Nurlaila; Slamet, Alim Setiawan; Sembiring, Indra Refipal (Universitas Merdeka Pasuruan, 2025)
Advances in technology, information, and communication, particularly the internet in the 21st century, have created new opportunities for companies to optimize their online marketing strategies. L’Oréal Paris, a leading global cosmetics brand, has transitioned from offline to online sales. Ecommerce platforms provide review and rating features that enable consumers to give feedback on products and services, including details about condition, authenticity, quality, and product suitability. This study aims to analyze the impact of online customer reviews and ratings on the purchasing decisions for L'Oréal products. This research was conducted from June to July 2024, involving 402 respondents using a non probability sampling technique and purposive sampling method. Primary data collected through questionnaires and secondary data from literature studies. The data analysis methods employed were descriptive analysis and SEM-PLS. The results of this study indicate that online customer reviews and ratings have a significant and positive impact on purchase decisions.